Isolated rat hepatocytes can signal to other hepatocytes and bile duct cells by release of nucleotides. - Schlosser, S F (1996)
Intercellular communication among certain cell types can occur via ATP secretion, which leads to stimulation of nucleotide receptors on target cells. In epithelial cells, however, intercellular communication is thought to occur instead via gap junctions. Here we examined whether one epithelial cell type, hepatocytes, can also communicate via nucleotide secretion. The effects on cytosolic Ca2+ ([Ca2+]i) of mechanical stimulation, including microinjection, were examined in isolated rat hepatocytes and in isolated bile duct units using confocal fluorescence video microscopy. Mechanical stimulation of a single hepatocyte evoked an increase in [Ca2+]i in the stimulated cell plus an unexpected [Ca2+]i rise in neighboring noncontacting hepatocytes. Perifusion with ATP before mechanical stimulation suppressed the [Ca2+]i increase, but pretreatment with phenylephrine did not. The P2 receptor antagonist suramin inhibited these intercellular [Ca2+]i signals. The ATP/ADPase apyrase reversibly inhibited the [Ca2+]i rise induced by mechanical stimulation, and did not block vasopressin-induced [Ca2+]i signals. Mechanical stimulation of hepatocytes also induced a [Ca2+]i increase in cocultured isolated bile duct units, and this [Ca2+]i increase was inhibited by apyrase as well. Finally, this form of [Ca2+]i signaling could be elicited in the presence of propidium iodide without nuclear labeling by that dye, indicating that this phenomenon does not depend on disruption of the stimulated cell. Thus, mechanical stimulation of isolated hepatocytes, including by microinjection, can evoke [Ca2+]i signals in the stimulated cell as well as in neighboring noncontacting hepatocytes and bile duct epithelia. This signaling is mediated by release of ATP or other nucleotides into the extracellular space. This is an important technical consideration given the widespread use of microinjection techniques for examining mechanisms of signal transduction. Moreover, the evidence provided suggests a novel paracrine signaling pathway for epithelia, which previously were thought to communicate exclusively via gap junctions.